Diversity of orchids of the summit region in Genting Highlands, Malaysia - Ng, Yong Jin (2011)
An inventory of orchid species diversity was carried out in cloud forest habitat of the Summit Region in Genting Highlands, which is one of the most developed highland regions in Peninsular Malaysia. Since 1967, construction of roads and hotel complexes has had a serious destructive impact on its physical environment and vegetation. Habitat destruction together with climate change might cause some orchid species to be extirpated locally or extinct. However, no comprehensive study on orchid diversity was conducted in this region after Benjamin C. Stone in 1978. Therefore, this study is essential to reveal the current orchid diversity of the Summit Region in Genting Highlands after a gap of three decades. The orchid species of Summit Region in Genting Highlands, including Gunung Ulu Kali, Gunung Chin Chin and Gunung Lari Tembakau were surveyed. Eight plots of 10 m x 10 m were established to study the orchid diversity and all orchids found in cloud forest habitat which is above 1500 m were recorded. An updated checklist of orchid species of Summit Region in Genting Highlands was developed with data from current survey and works done by previous researchers. As a result, 146 orchid taxa were recorded, which comprises of 51 genera, 143 species, 1 subspecies and 2 varieties, out of which 46 of them are new records to Summit Region in Genting Highlands. Thirty-four taxa are endemic to Peninsular Malaysia, of which 19 are endemic to Pahang, Perak and Selangor states, and 1 species, Corybas villosus J.Dransf. & G.Sm. is endemic to Summit Region in Genting Highlands. The diversity indices used revealed that Summit Region in Genting Highlands has a moderately high diversity of orchid species. However, most of the orchid species in this region are very susceptible to extinction due to loss of habitat and climate change. An assessment of conservation status according to IUCN criteria revealed that 47 orchid taxa from Summit Region in Genting Highlands were threatened with extinction. Conservation actions are proposed to conserve the orchid diversity in Summit Region in Genting Highlands.